Sources of the Persistent Gender Wage Gap along the Unconditional Earnings Distribution : Findings from Kenya - Agesa, Richard U.; Agesa, Jacqueline; Dabalen, Andrew (Taylor and Francis, 2013)
Past studies on gender wage inequality in Africa typically attribute the gender pay gap either to gender differences in characteristics or in the return to characteristics. The authors suggest, however, that this understanding of the two sources may be far too general and possibly overlook the underlying covariates that drive the gender wage gap. Moreover, past studies focus on the gender wage gap exclusively at the conditional mean. The authors go further to evaluate the partial contribution of each wage-determining covariate to the magnitude of the gender pay gap along the unconditional earnings distribution. The authors' data are from Kenya, and their empirical technique mirrors re-centered influence function regressions. The authors' results are novel and suggest that while gender differences in characteristics and the return to characteristics widen the gender pay gap at the lower end of the wage distributions, gender differences in characteristics widen the gender wage gap at the upper end of the wage distributions. Importantly, the authors find that the underlying covariates driving gender differences in characteristics and the return to characteristics are the industry, occupation, higher education and region covariates. In the middle of the distributions, however, the authors find that gender differences in the return to characteristics, fueled by education and experience covariates, exert the strongest influence on the magnitude of the gender pay gap.